Developing Tailored Messages to Improve Mental Health and Adjustment of Asian International Students - Jin, Lan; Acharya, Lalatendu (Journal of International Students, 2022)
The purpose of the study was to develop tailored messages improving mental health and adjustment of Asian international students (AIS) in the US. The PEN-3 cultural model was used to contextualize the role of culture in mental health needs of AIS. Messages were developed through a multi-step participatory process with consisting of three focus groups (n=15), thirteen individual interviews, one expert consultation, and finally an online survey (n=85). The study led to the development of seven broad themes with seven tailored messages under each theme (total 49). Seven broad themes were: increasing the awareness of mental health and reducing stigma; motivational quotes; available and accessible resources for AIS to improve mental health; seeking help from social network and developing interpersonal skills; adjusting to American culture and college life; coping strategies to reduce stress and improve mental health and adjustment; and safety issues. The implications for culturally responsive programs are discussed.